2020
DOI: 10.3390/ijms21165761
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms of Bisphenol A (BPA) Contributing to Human Disease

Abstract: Bisphenol A (BPA) is an organic synthetic compound serving as a monomer to produce polycarbonate plastic, widely used in the packaging for food and drinks, medical devices, thermal paper, and dental materials. BPA can contaminate food, beverage, air, and soil. It accumulates in several human tissues and organs and is potentially harmful to human health through different molecular mechanisms. Due to its hormone-like properties, BPA may bind to estrogen receptors, thereby affecting both body weight and tumorigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
153
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(158 citation statements)
references
References 175 publications
(212 reference statements)
0
153
0
5
Order By: Relevance
“…An additional mechanism of BPA action involves the modulation of epigenetic mechanisms through changes in DNA methylation, histone modification and changes in microRNA expression. Reviews of BPA-induced epigenetic changes have been provided by several authors [ 152 , 153 ]. The transgenerational epigenetic inheritance of changes in glucose homeostasis in animal studies induced by BPA through histone modifications affecting PDX1 and insulin-like growth factor 2 ( IGF2 ) expression have been documented [ 154 , 155 ].…”
Section: Resultsmentioning
confidence: 99%
“…An additional mechanism of BPA action involves the modulation of epigenetic mechanisms through changes in DNA methylation, histone modification and changes in microRNA expression. Reviews of BPA-induced epigenetic changes have been provided by several authors [ 152 , 153 ]. The transgenerational epigenetic inheritance of changes in glucose homeostasis in animal studies induced by BPA through histone modifications affecting PDX1 and insulin-like growth factor 2 ( IGF2 ) expression have been documented [ 154 , 155 ].…”
Section: Resultsmentioning
confidence: 99%
“…The packaging of ultra-processed and processed foods adds an additional layer of concern. Synthetic compounds like bisphenol A (BPA) are omnipresent in food packaging, and BPA in particular has been shown to act as a xenohormone with the potential to impair reproductive function in men and increase cancer risk ( 19 ). While some manufacturers have responded to the public's concerns about BPA exposure by switching to bisphenol S (BPS), research indicates that this alternative may actually be more readily absorbed into the body ( 27 ).…”
Section: Concerns Surrounding the Intake Of Ultra-processed Foodsmentioning
confidence: 99%
“…UPF deliver a poor nutrient profile (15) and their additives disrupt gut function (16)(17)(18). The packaging, while attractive, may be adding additional health risks (19,20). To date, only one randomized controlled trial assessing the impact of UPF on cardio-metabolic health has been published, and the findings suggest that UPF consumption can lead to passive overeating and subsequent weight gain (21).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the toxic compounds, the best studied candidate is BPA, which has been shown to stimulate the development of metabolic dysfunction in animal models by epigenetic mechanisms (see [ 233 , 234 ] for review). Several of the factors identified in animal studies have subsequently been also found in human samples.…”
Section: Perspectivesmentioning
confidence: 99%